กึ่งกรุปย่อยปกติและสมาชิกปกติบางตัวของกึ่งกรุป Tp,x - พชร พลอยเพ็ชร์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
In this project, let X be a nonempty finite set. We study the subsemigroup Tp,x of the full transformation semigroup on X and a subset Tp,k of Tp,x such that Tp,k is a regular subsemigroup under composition. Finally, we provide some regular elements in Tp,x - Tp,k